Pengaruh Bekisting Multiplek dan Papan Kayu terhadap Kuat Tekan Beton - Anggi Febriandy; Elvira Elvira; Eti Sulandari (Universitas Batanghari Jambi, 2026)
Formwork is a critical component in concrete construction as it functions as a temporary mold that can influence concrete quality, particularly during placement and early curing stages. In construction practice, especially in small- to medium-scale projects, timber formwork is still widely used due to economic considerations; however, its water-absorbing characteristics may reduce concrete compressive strength. As an alternative, plywood formwork and various surface coatings have been applied, yet their comparative influence on concrete compressive strength has not been extensively evaluated in a systematic manner. This study aims to analyze the effect of formwork material and surface coating type on the 28-day compressive strength of concrete. An experimental laboratory method was employed using cubic specimens measuring 15×15×15 cm, with two target concrete grades of 20 MPa and 30 MPa. The variations included steel, timber, and plywood formwork, combined with plastic sheet coating, release oil, and oil-based paint. Compressive strength testing was conducted at 28 days, and the results were analyzed using a descriptive–comparative approach with steel formwork as the reference. The results indicate that plywood-based formwork, particularly plywood coated with oil-based paint, produced compressive strength values closest to the reference. In contrast, timber-based formwork showed greater reductions in compressive strength across both concrete grades. Based on these findings, the use of plywood formwork with paint coating is recommended as a more reliable alternative to timber formwork under similar testing conditions.